Racked and stacked - James, Lorelei (James, Lorelei. Blacktop cowboys novel., 2020)
"Opposites don't just attract in the West--they sizzle--and Wyoming has never been hotter than in the latest sexy Blacktop Cowboys novel from the New York Times bestselling author of Hang Tough. Growing up with three older brothers, Larissa "Riss" Thorpe defines the term tomboy--a moniker that never mattered to her until she crossed paths with sexy cowboy playboy, Ike Palmer. His declaration that he prefers his women soft and feminine is the one benefit to becoming his business partner. Since Riss is obviously not his type, there's little chance they'll mix business and pleasure when they're in close quarters on the road together. Former cattle broker Ike Palmer was ready for a new chapter in his life when he partnered with Riss, a contrary redhead who lords her mechanical abilities over him at every turn. Ike raised his three younger sisters; he knows a thing or three about how women work. The problem is ... Riss is unlike any woman he's ever met. With the odds stacked against them, Riss and Ike will have to choose between the stubbornness that keeps them apart and the fiery attraction that could lead to something more.."--